(untitled) (Annals of Medical Research, 2021)
The COVID-19 pandemic that emerged in Wuhan, Hubei Province, China in December 2019 is ongoing. COVID-19 may also cause neurological symptoms with central or peripheral nervous system or skeletal muscle involvement. Guillain–Barré syndrome (GBS) is an autoimmune disorder of the peripheral nervous system that is usually triggered by bacterial or viral infections. Autonomic nerve involvement can be seen in GBS. Case reports suggest that GBS is linked to COVID-19 infection. Here, we present a case of GBS occurring after COVID-19, accompanied by dysautonomia.